Association between Exposure to the Chinese Famine in Different Stages of Early Life and Decline in Cognitive Functioning in Adulthood - Wang, Chao; An, Yu; Yu, Huanling; Feng, Lingli; Liu, Quanri; Lu, Yanhui; Wang, Hui; Xiao, Rong (Frontiers in Behavioral Neuroscience, 2016)
Objective: To investigate whether exposure to the Chinese Famine in different life stages of early life is associated with cognitive functioning decline in adulthood. Methods: We recruited 1366 adults born between 1952 and 1964 and divided them into fetal-exposed, early childhood-exposed (1-3 years old during the famine), mid childhood-exposed (4-6 years old during the famine), late childhood-exposed (7-9 years old during the famine) and non-exposed groups. A selection of cognitive tests was administered to assess their cognitive performance. Association between malnutrition in different famine exposure periods and adult cognitive performance was estimated by multivariate logistic and multiple linear regression analyses. Results: There were significant differences in cognitive performance between subjects exposed to famine during different life stages. For the general cognitive tests, fetal-exposed period was associated with decreased scores of the Mini-Mental Status Examination (MMSE) and late childhood-exposed with decreased scores of the Montreal Cognitive Assessment (MoCA). We also found exposure to famine during mid and late childhood was associated with worse performance on the Stroop color and word test. Conclusion: Famine exposure in utero and during childhood is associated with overall and specific cognitive decline, affecting selective attention and response inhibition particularly.